Susceptibility of a panel of virulent strains of Mycobacterium tuberculosis to reactive nitrogen intermediates. - Rhoades, E R (1997)
Murine bone marrow-derived macrophages were infected with a panel of virulent isolates of Mycobacterium tuberculosis including laboratory strains Erdman and H37Rv and various clinical isolates in order to determine the sensitivity of each of these strains to the antimycobacterial activities of macrophage-generated reactive nitrogen intermediates (RNI). All of the M. tuberculosis strains grew in murine bone marrow-derived macrophages; however, gamma interferon-primed macrophages limited the initial growth of intracellular bacilli. Some of the mycobacterial strains, including Erdman, were killed over the first 4 days of infection, as evidenced by significant decreases in the number of viable intracellular bacilli determined by a CFU assay. Other mycobacterial strains were not killed during this same period, and some isolates, including CSU 24 and CSU 31, grew steadily in activated macrophages. The accumulation of nitrite on infected monolayers was measured, and it was found that inhibitory levels of RNI did not vary among infections with the different strains. Nitrite tolerance was determined in a cell-free system for each of the strains in order to compare susceptibilities of the strains to RNI. All of the strains tested were killed by levels of RNI generated by the acidification of 10 mM NaNO2 to pH 6.5 or 5.5, and the strains exhibited a range of tolerance to lower concentrations of RNI. No correlations were observed between such cell-free RNI tolerances and the capacity of bacilli to resist macrophage RNI-mediated killing. These results indicate that under stringent conditions, RNI can kill M. tuberculosis, but that under less harsh, more physiological conditions, the effects of RNI range from partial to negligible inhibition.